Self Nano-Emulsifying Drug Delivery System (SNEDDS) of Curcuma Mangga Val. Essential Oil and The Stability Study - Sudibyo, Retno Sunarminingsih; Mahdi, Lukman; Martien, Ronny (Indonesian Journal of Pharmacy, 2020)
Essential oil of Curcuma mangga Val. has been reported to have cytotoxic effect against cancer cell lines. But this oil is unstable in dispensing so that a self nano-emulsifying drug delivery system (SNEDDS) of the oil was conducted to solve the problem and improve its potency. In the study, optimization, verification, characterization, and stability test of the SNEDDS formula were carried out respectively by simplex lattice design (SLD) on Design Expert ver. 10 software, droplet size and Zeta potential determinations using particle size analyzer (PSA) instrument, as well as heating-cooling and freeze-thaw methods. The best SNEDDS formula resulted was Miglyol : Tween 80 : PEG 400 = 16.034% : 68.380% : 15.586%; with transmittance of 84.47 + 1.05%, droplet size of 15.75 nm, zeta potential of -8.54 mV, polydispersity index (PDI) of 0.188, emulsifying time of 49.67 + 1.7 seconds in distilled water, 24.33 + 4.19 seconds in artificial gastric fluid and 21.33 + 2.87 seconds in artificial intestine fluid. After a freeze-thaw test there was no change on the emulsion’s clarity, color, smell, as well as no separation, which means that the formula was stable thermodynamically. The optimum SNEDDS formula resulted has small particle size, better emulsifying time in artificial gastric and intestine fluids, as well as better thermodynamic stability, which in turn will improve the cytotoxic activity of the Curcuma mangga Val. rhizome oil toward cancer cells.